AB112. Constructing several amiRNAs with multiple targets to silence selectively cancer gene and to inhibit the growth of bladder cancer cells - Xin, Fu (Transl Androl Urol, 2014)
BACKGROUND: Bladder cancer is the most common malignant tumor of urinary system, with the highest incidence of genitourinary dysfunction in China. Current treatments include the traditional surgery, radiotherapy and chemotherapy, however the effect are not satisfied. Therefore, it is necessary to seek a new method to treat bladder cancer. Using the method of synthetic biology, in combination with a technique called RNA interference, it may bring a new hope for the treatment of bladder cancer. MicroRNA which is a class of endogenous non-coding RNA and found in eukaryotes, has the function of regulation and control of the expression of genes, its size is about 20-25 nucleotides. It can inhibit the expression of the purpose gene by RNA interference. PURPOSES: Constructing few artificial miRNAs to selectively silence oncogenes which are expressed highly in bladder cancer, and to suppress the proliferation and migration, promote apoptosis of bladder cancer. METHODS: This study selects several genes to study, which are closely related to bladder cancer, such as UCA1, MALAT1, HRAS and MYC. UCA1 and MALAT1 are non-coding genes, HRAS and are coding genes. By constructing three amiRNAs (includingamiRNA-UCA1-MALAT1, amiRNA-HRAS-MYC andamiRNA-HRAS-UCA1), we can silence two different genes at the same time. And we can also get three different combinations (including non-coding gene+ non-coding genes, coding genes coding genes, coding genes+ non-coding genes). In the end, we can achieve the purpose of the treatment of bladder cancer by treating multiple genes and targets. RESULTS: Three amiRNAS that we build for the experiment can selectively silence UCA1, MALAT1, HRAS and MYC, make the expression of them decrease, inhibit growth and migration, and promote apoptosis of bladder cancer cells.